Body mass index values for term newborns and its correlation with other anthropometric surrogates - Kamalammal, Rugmini; Rao, Soorya; Parameaswari, P. J. (International Journal of Contemporary Pediatrics, 2016)
Background: Body mass index is a better tool as it relates two anthropometric measures - Weight and Length. This study aims at identifying the mean BMI in term new-borns in Asian population and also the correlation between BMI and other anthropometric surrogates for birth weight. Methods: Cross Sectional study was conducted in a tertiary care hospital by taking anthropometric measurements for 339 consecutive term newborns, born in the institution. Mean BMI was 11.784 ±1.7. Moderate Positive correlation was observed between BMI and Mid Arm Circumference (r= +0.401; P=0.000). Results: The cut off value for BMI to identify LBW was 13. Mid Arm Circumference, Chest circumference and Head circumference correlated well with BMI. Conclusions: By trial and error method of analysis we recommend BMI value of 13 as a cut off for identifying low birth weight infants. BMI is seen to be better than Birth weight in assessing body proportion of a new born.